2022
DOI: 10.1007/s00424-022-02695-7
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing retinal phagocytes to combat pathological neovascularization in ischemic retinopathies?

Abstract: Ischemic retinopathies (IR) are vision-threatening diseases that affect a substantial amount of people across all age groups worldwide. The current treatment options of photocoagulation and anti-VEGF therapy have side effects and are occasionally unable to prevent disease progression. It is therefore worthwhile to consider other molecular targets for the development of novel treatment strategies that could be safer and more efficient. During the manifestation of IR, the retina, normally an immune privileged ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 122 publications
(201 reference statements)
0
8
0
Order By: Relevance
“…The spontaneous reparative vascular regression at the late stage of diseases usually attenuates the destructive costs and implications of the pathological neovessels [167]. This is supported by the fact that almost 90% of all affected ROP infants in the United States recover spontaneously without any therapeutic intervention [166,168,169]. Spontaneous regression of the pathological neovessels was also reported in DR individuals [170,171].…”
Section: Beneficial Effect: Vascular Remodelingmentioning
confidence: 96%
See 3 more Smart Citations
“…The spontaneous reparative vascular regression at the late stage of diseases usually attenuates the destructive costs and implications of the pathological neovessels [167]. This is supported by the fact that almost 90% of all affected ROP infants in the United States recover spontaneously without any therapeutic intervention [166,168,169]. Spontaneous regression of the pathological neovessels was also reported in DR individuals [170,171].…”
Section: Beneficial Effect: Vascular Remodelingmentioning
confidence: 96%
“…A growing body of evidence supports the significance of the inflammation and pro-inflammatory mediators in driving proliferative retinopathies and pathological neovascularization [177][178][179][180]. Stressed retinal cells boost local inflammation and recruit immune cells to the ischemic retina [168]. Stressed endothelial cells, for example, enhance leukocyte adhesion and transmigration in microvessels via upregulating adhesion molecules (ICAM-1, VCAM-1, etc.)…”
Section: Beneficial Effect: Vascular Remodelingmentioning
confidence: 99%
See 2 more Smart Citations
“…indicated that peripheral macrophage depletion significantly inhibits pathological retinal neovascularization in OIR model in mice ( 25 ). Activation of mononuclear phagocytes may participate in the pathogenesis and development of ischemic retinopathies including ROP, which provide a new promising target in preventing these diseases ( 26 ). As the key drivers of immune responses, peripheral blood mononuclear cells (PBMCs) are comprised of variety types of immune cells, such as lymphocytes (T cells, B cells and natural killer cells), monocytes and dendritic cells ( 27 ).…”
Section: Introductionmentioning
confidence: 99%